The feasibility of retained ownership strategies for cow-calf producers - Albright, Kay (Kansas State University, 2011)
Retained ownership can generally be described as when a producer does not sell his or her calf crop immediately after weaning but keeps the calves for an extended period of time. This is a decision that is made by the cow-calf producer every year and may or may not change from year to year. For some, the decision is based on past practices while others will evaluate the market before making a decision. There are various levels of retained ownership that can be modified to fit a producer’s operation and can range from a preconditioning program to finishing the cattle in the feedlot. This study specified various retained ownership scenarios in order to be able to analyze the situations. Budgets were used to analyze the optimum phase of production at which to sell calves that is most profitable while taking risk into consideration. Specifically, budgets were developed for scenarios of four cow-calf herds, four backgrounding phases, two grazing phases, and six custom feedlot phases. These budgets were used to produce sixteen potential retained ownership scenarios. The scenarios range from selling the calves immediately after weaning to owning the cattle through finishing at the feedlot. Each scenario was then analyzed based on the net returns over a 10-year period. Additionally, the scenarios were analyzed based on net returns over feed costs. Target MOTAD was used to analyze the risk component of the scenarios. Although most of the net returns were negative for all scenarios, retained ownership showed a trend of improving net returns. However, along with the improved returns came a greater variability in returns which is unattractive to a risk adverse producer. Target MOTAD results on a net return basis selected the cow-calf only phase of production in all scenarios.
Keywords: Retained ownership; Economics, Agricultural (0503)